Study on Prevalence and Antibiotic Profiling of Enterococcus Spp. from Chicken Meat - Parmar, Nilam N.; Brahmbhatt, Manoj N.; Parmar, Bhupendra C.; Goswami, Mayank; Thakur, Sonali; Dubey, Shreya (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was undertaken to characterize Enterococcus species isolated from poultry meat by cultural isolation, PCR detection  and antibiogram. Antibiotic profiling of detected Enterococcus spp. isolates were done by disc diffusion method. Total 150 chicken meat  samples were examined for the presence of Enterococcus spp. The overall prevalence of Enterococcus spp. by cultural isolation was 56%.  The prevalence of Enterococcus spp. by targeting tuf gene and ddlE.faecalis  gene in PCR was 95.23 and 77.38%, respectively. In the  antibiotic sensitivity test, Enterococcus isolates showed high resistance toward Erythromycin and Tetracycline. However, low resistance  was seen towards Chloramphenicol, whereas all the isolates were susceptible to Gentamicin.This study found a high prevalence of multi drug resistance among enterococci isolated from poultry meat, suggesting that these resistant bacteria and genes may be transported  from food to humans and pose a significant risk to human health in the coming years.
Keywords: Antibiotic resistance; Chicken meat; Enterococcus; PCR